Estructura familiar y vínculos afectivos en adultos jóvenes de una Universidad de Tunja (2023)
The present research describes the characteristics of the family structure and the formation of interpersonal affective bonds, specifically in young adults between 20 and 30 years of age from a private university in Tunja. A sample of 50 participants was taken, who answered the sociodemographic form, the Test for the Evaluation and Assessment of Interpersonal Bonds in Adults and the Family Cohesion and Adaptability Evaluation Scale (FACES III). The results of the sociodemographic data showed that most of the young adults come from families of origin, while 98% of the participants are in university education, the predominant marital status is single and 96% do not have children